Histoprotective Effect of Essential Oil from Citrus aurantifolia in Testosterone-Induced Benign Prostatic Hyperplasia Rat. (25th September 2019) - Acheampong, Desmond O.; Barffour, Isaac K.; Boye, Alex; Asiamah, Ernest A.; Armah, Francis A.; Adokoh, Christian K.; Oluyemi, Joy F.; Adrah, Benjamin; Opoku, Richard; Adakudugu, Emmanuel
Abstract : Background . Benign prostatic hyperplasia (BPH) is a common urological disorder reported among ageing men. Objective . The study assessed histoprotective effect of lime essential oil (LEO) in a rat model of testosterone-induced benign prostatic hyperplasia (BPH) and evaluated its ability to reverse testosterone-mediated changes in the testis, kidney, and liver. Materials and Methods . Adult Sprague Dawley (aged 12 weeks, 240–390 g) male rats were intramuscularly injected with testosterone enanthate (TE) (10 mg/kg) reconstituted in olive oil for ten days to establish benign prostatic hyperplasia (serum PSA level ≥ 1.24 ng/ml) in. After confirmation of BPH (sustained serum PSA level ≥ 1.24 ng/ml), rats in all groups (LEO: 30, 100, and 300 mg/kg, po, n  = 6; finasteride: 15 mg/kg, po, n  = 6) except model (BPH without treatment) and sham (no BPH and no treatment) groups were treated for 21 days. At the end of treatment, rats were anesthetised and blood was collected via cardiac puncture to determine serum PSA and total antioxidant capacity (TAC) levels. The prostate gland, testis, kidney, and liver were harvested, weighed, histologically processed and stained with H&E. Results . LEO- and finasteride-treated groups recorded lesser mean prostatic weights relative to their model group. Baseline mean serum PSA level of LEO- and finasteride-treated groups reduced significantly (p < 0.05 ) relative to model group. Serum TAC levels were also higher in LEO- and finasteride-treated groups relative to model group. LEO-treated groups had less thickened glandular epithelium, smaller acini, fewer prostatic secretions and more fibromuscular stroma relative to model group. LEO and finasteride treatment produced improved histomorphological characteristics of testis, kidney, and liver compared to model group. Conclusion . By the current results, Citrus aurantifolia LEO may possess active agents that can be explored for translational medicine against BPH.